2006
DOI: 10.1055/s-2005-865818
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Analysis of the Golf Swing in Men and Women Experienced Golfers

Abstract: Golf has become an increasingly popular sport, which is enjoyed by both men and women. This paper addresses the question what differences may exist between men and women golfers. The purpose of this study is to analyze the kinematic pattern of the golf swing in both men and women experienced golfers. Seven male and five female golfers participated in the study. The measurements of kinematic data during swing were obtained with the optoelectronic system VICON (Oxford's Metric, Oxford, UK) with five cameras oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
52
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 14 publications
8
52
2
2
Order By: Relevance
“…While expert golfers regulate their downswing amplitude to appropriately control club head force for different putting distances, novices do not show this amplitude-distance relation (see also Sim & Kim, 2010). Despite work examining skill-level differences in attentional control (e.g., Beilock, Bertenthal, McCoy, & Carr, 2004;Beilock, Carr, MacMahon, & Starkes, 2002) and movement differences in novice and skilled perceptual-motor performance (Delay et al, 1997;Egret, Dujardin, Weber, & Chollet, 2004), relatively few studies have explored how the attentional demands of performance directly relate to movement -and how this might differ as a function of skill level. Insight into this relation is important for developing a comprehensive understanding of what makes a novice performer different from his/her highly-skilled counterpart, and may also shed light on how to optimize skill learning and prevent skill breakdown (e.g., in pressure-filled high-stakes situations) once high-level performance has been achieved.…”
Section: Introductionmentioning
confidence: 95%
“…While expert golfers regulate their downswing amplitude to appropriately control club head force for different putting distances, novices do not show this amplitude-distance relation (see also Sim & Kim, 2010). Despite work examining skill-level differences in attentional control (e.g., Beilock, Bertenthal, McCoy, & Carr, 2004;Beilock, Carr, MacMahon, & Starkes, 2002) and movement differences in novice and skilled perceptual-motor performance (Delay et al, 1997;Egret, Dujardin, Weber, & Chollet, 2004), relatively few studies have explored how the attentional demands of performance directly relate to movement -and how this might differ as a function of skill level. Insight into this relation is important for developing a comprehensive understanding of what makes a novice performer different from his/her highly-skilled counterpart, and may also shed light on how to optimize skill learning and prevent skill breakdown (e.g., in pressure-filled high-stakes situations) once high-level performance has been achieved.…”
Section: Introductionmentioning
confidence: 95%
“…Others used the coined term 'X-factor' to describe the relationship between the trunk and pelvis rotations. In the golf biomechanical literature, body rotation, typically quantified by axial rotation of the central body segments, has been widely investigated and linked to performance outcomes, such as clubhead velocity [19,38,39]. Many studies have reported pelvis and trunk axial rotational angles at various stages of the swing including at TA, TB, IMP, middownswing, last 40ms prior to impact as well as the peak magnitudes.…”
Section: Pelvic Rotation [Is] Rotation Around Its Mid Axisbut Imentioning
confidence: 99%
“…The significance level was set at an alpha level of 0.05. (Egret et al, 2005). Table 2 reports the hip rotational velocities for each hip during the golf swing.…”
Section: Research Articlementioning
confidence: 99%